Ionosphere Monitoring in South East Asia in the ERICA Study. Issue 2 (19th June 2017) - Povero, Gabriella; Alfonsi, Lucilla; Spogli, Luca; Di Mauro, Domenico; Cesaroni, Claudio; Dovis, Fabio; Romero, Rodrigo; Abadi, Prayitno; Le Huy, Minh; La The, Vinh; Floury, Nicolas
Abstract: The ERICA study aims to find out signatures of the interplay between the magnetosphere‐geomagnetic field and the ionosphere that degrade trans‐ionospheric signals such as those transmitted by GNSS satellites. The project activity focuses on the characterization of the ionospheric variability of the Equatorial Ionospheric Anomaly in the South East Asian region through the analysis of datasets collected with an ad hoc measurements campaign. The campaign has been conducted with ground‐based instruments located in the footprints of the Equatorial Ionospheric Anomaly and Equatorial Ionospheric Trough. This paper presents some of the relevant results achieved by the project, in terms of ionospheric climatology and weather assessment over the interested area. In particular, the paper describes the average condition of the Equatorial Ionospheric Anomaly recorded during the entire campaign and provides interesting insights on relevant scintillation events. Copyright © 2017 Institute of Navigation